Essential oils of aromatic Egyptian plants repel nymphs of the tick Ixodes ricinus (Acari: Ixodidae) - El-Seedi, H.R.; Azeem, M.; Khalil, N.S.; Sakr, H.H.; Khalifa, S.A.M.; Awang, Khalijah; Saeed, A.; Farag, M.A.; AlAjmi, M.F.; Pålsson, K.; Borg-Karlson, A.K. (Kluwer (now part of Springer), 2017)
Due to the role of Ixodes ricinus (L.) (Acari: Ixodidae) in the transmission of many serious pathogens, personal protection against bites of this tick is essential. In the present study the essential oils from 11 aromatic Egyptian plants were isolated and their repellent activity against I. ricinus nymphs was evaluated Three oils (i.e. Conyza dioscoridis L., Artemisia herba-alba Asso and Calendula officinalis L.) elicited high repellent activity in vitro of 94, 84.2 and 82%, respectively. The most active essential oil (C. dioscoridis) was applied in the field at a concentration of 6.5 µg/cm2 and elicited a significant repellent activity against I. ricinus nymphs by 61.1%. The most repellent plants C. dioscoridis, C. officinalis and A. herba-alba yielded essential oils by 0.17, 0.11 and 0.14%, respectively. These oils were further investigated using gas chromatography-mass spectrometry analysis. α-Cadinol (10.7%) and hexadecanoic acid (10.5%) were the major components of C. dioscoridis whereas in C. officinalis, α-cadinol (21.2%) and carvone (18.2%) were major components. Artemisiaherba-alba contained piperitone (26.5%), ethyl cinnamate (9.5%), camphor (7.7%) and hexadecanoic acid (6.9%). Essential oils of these three plants have a potential to be used for personal protection against tick bites.